2021
DOI: 10.32539/bji.v7i2.283
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Patterns of Deep Neck Infection in Dr. Mohammad Hoesin General Hospital Palembang 2020

Abstract: Intoduction: Deep neck infection is the accumulation of pus in the potential space and facial area in the deep neck. The incidence of deep neck space infections is 1/100.000 in adults and 2/100.000 in children. Risk factors such as age, oral hygiene, and comorbidities such as DM are predisposed factors in deep neck infection. Effective pus collection of specimens is essential, to obtain the organisms and determine the effective antibiotics. Purpose: The aim of this study was to describe the characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Brito et al 4 found that the average symptom onset was 8 days, and according to the study of Yanti et al 16 that the onset of symptoms until the patient was diagnosed with a deep-neck abscess was mostly 0-1 week (52.7%). Chuan et al 17 reported that symptom onset was found in a group of patients from local regions with a duration of 1-12 days with a mean of 5.3 days, while in the group living in urban areas, a duration of 1-10 days with an average of 5.3 days.…”
Section: Discussionmentioning
confidence: 99%
“…Brito et al 4 found that the average symptom onset was 8 days, and according to the study of Yanti et al 16 that the onset of symptoms until the patient was diagnosed with a deep-neck abscess was mostly 0-1 week (52.7%). Chuan et al 17 reported that symptom onset was found in a group of patients from local regions with a duration of 1-12 days with a mean of 5.3 days, while in the group living in urban areas, a duration of 1-10 days with an average of 5.3 days.…”
Section: Discussionmentioning
confidence: 99%
“…16,37 Our study was in accordance with Pranata, et al (2014), who reported nodular subtypes as the most common subtype, accounting for 63% of all BCC, followed by nodulo-infiltrative (16%), infiltrative (6.2%), nodulopigmented (9.3%), fibroepithelioma (0.6%), basosquamous (2.5%), superficial (1.2%) and micronodular (1.2%) (Table 5). 32…”
Section: There Were Reports Of Escalating Incidents In Severalmentioning
confidence: 99%